Keefektifan Pelapisan Benih terhadap Peningkatan Mutu Benih Padi Selama Penyimpanan - Ikrarwati, Ikrarwati; Ilyas, Satriyas; Yukti, AmiyarsI Mustika (Pusat Penelitian dan Pengembangan Tanaman Pangan, 2015)
Seed coating using biological pesticides such as clove oil and citronella oil, was expected to have the ability to control seed-borne pathogens on rice. The aim of the research was to determine the effectiveness of seed coating using clove oil and lemon grass oil against seed-borne fungi and bacteria on rice seed variety â€œHipa 8â€ during storage. The experiment was conducted in Cimanggis, from February to September 2012, using completely randomized design with single factor, consisting of four levels: (1) clove oil 1% + chitosan 3%; (2) lemon grass oil 2% + carboxymethyl-cellulose 1%; (3) Synthetic pesticide (streptomycin sulphate 0.04% + benomyl 0.1%) + arabic gum 10%; and (4) control (without coating). Results showed that seedborne fungi pathogens on seed of Hipa 8 rice were detected at 6-month storage consisted of Fusarium sp., Curvularia sp., Alternaria sp., Cladosporium sp., Aspergillus sp. and Penicillium sp. The detected pathogenic bacteria were Xanthomonas oryzae pv. oryzae and X. campestris pv. oryzicola. Coating formula most compatible with the rice seed of HIPA 8 was chemical pesticide + 10% arabic gum, which suppressed fungal infection from 80% to 45% at the first month and from 90% to 70% at the fifth month, suppressed populations of Xoo + Xco from 7.6 x 108 cfu/g of seed to 5.86 x 105 cfu/g of seed at the first month and 7.0 x 106 cfu/g of seed to 1.4 x 104 cfu/g of seeds at the sixth month. The treatment caused the smallest decrease of seed viability compared to the other coating treatments.